Malaria As An Important Cause Of Maternal Mortality In Sudan - Mohamed EL Sanousi, Mohamed EL Sanousi; AL Hassan, Abdul Rahman Abdul Hafeez; Abd EL Salam, Muawia Mohamed Ahmed (Gezira Journal of Health Sciences, 2004)
This study was performed to highlight the role of malaria in pregnancy as  an important cause  of maternal mortality. It reviewed the previous studies, conference presentations and postgraduate thesis . Malaria found to be the cause of death of 10.26% to 46.7% of MM. The 1998 to 2003 records of maternal deaths of Wad Medani Obstetrics and gynaecology  teaching hospital (WMOGTH) was retrospectively studies (malaria caused death of 8.82% to 39.7% The mean age was 27.57years , most of them were primigravidae and from rural areas.  37.8% of the deaths occured at 28-36 weak of gestation . The mean duration of stay in hospital was (3.22) days. 32.4% of deaths stayed for less than 24 hours This indicated  severe and serious clinical presentations. The main causes of death due to malaria or its complication  were anemae heart failure  (24.3%), cerebral malaria (21.6%) and  circulatory failure (8.1%). Others were pulmonary edema , hyperpyrexia  , puerperal psychosis , abortion , severe epistaxes , cardiac  arrest , black water fever, electrolyte imbalance, and hepatic failure. The study recommended effective prevention of malaria and an intensive care approach in its management.